2018
DOI: 10.22270/jddt.v8i1.1657
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species as Possible Mediator of Antibacterial Activity of Parkia Javanica, Against Bacterial Species Predominantly Found in Chronic Wound.

Abstract: The crude methanol extract of Parkia javanica was screened for antibacterial activity. against bacterial species predominantly found in chronic wound, by serial dilution technique. Growth kinetics study was performed and percentage of ROS production was measured by NBT reduction assay. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were obtained with a range of IC 100 5-40 mg/ml in case of standard bacterial strains. The lag phase of all extract treated bacteria is exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…[36,37] Several studies have reported the antibacterial, anti-inflammatory, and wound healing activities of P. javanica bark. [38][39][40][41] The methanolic extract of P. javanica bark (MEPJB) has also been reported to inhibit various blood cell malignancies. [42] However, there is no scientific study on the anti-colon cancer activity of P. javanica bark.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Several studies have reported the antibacterial, anti-inflammatory, and wound healing activities of P. javanica bark. [38][39][40][41] The methanolic extract of P. javanica bark (MEPJB) has also been reported to inhibit various blood cell malignancies. [42] However, there is no scientific study on the anti-colon cancer activity of P. javanica bark.…”
Section: Discussionmentioning
confidence: 99%
“…This plant is widely used by tribal population of northeast region of India 11,12,13 . In our previous study, it was found that, crude methanol extract of Parkia javanica possess antibacterial activity against both standard ATCC strains and MDR strains and ROS induced DNA damage may be possible mediator of antibacterial activity of this plant 14,15,16 . Therefore, this work has been undertaken to explore the active fraction of this study plant having antibacterial properties against gram negative multi drug resistant bacterial strains with possible mode of action.…”
Section: Introductionmentioning
confidence: 96%